Haematological Changes in Guinea Fowls (Numida meleagris galeata, Pallas) Following Haemorrhage - Olayemi, F.O. (International Journal of Poultry Science, 2009)
Haematological changes associated with haemorrhage were determined in the guinea fowl (Numida meleagris galeata, Pallas). The red blood cell, packed cell volume and mean corpuscular haemoglobin decreased significantly (p